THE ADMINISTRATOR’S COMPETENCY AND THE EFFECTIVENESS OF SCHOOL UNDER RATCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Chaloeichanya, Wanrudee; Inrak, Sangaun (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to: 1) Examine the competency of school administrators of school under Ratchaburi Primary Educational Service Area Office 2 2) Evaluate the effectiveness of school under Ratchaburi Primary Educational Service Area Office 2 3) Investigate the relationship between the competency of school administrators and school effectiveness of school under Ratchaburi Primary Educational Service Area Office 2. This study employs a descriptive research design and follows three phases 1) Research project preparation 2) Research implementation 3) Research report presentation. The study utilizes a one-shot, non-experimental case study approach, analyzing 108 schools under the Ratchaburi Primary Educational Service Area Office 2. Data were collected from two respondents per school, comprising one school director and one teacher, totaling 216 respondents. The research instrument employed was a questionnaire assessing administrator competency based on the conceptual framework of Hellriegel, Jackson, and Slocum, as well as school effectiveness based on the framework of Lunenburg and Ornstein. The statistical tools used for data analysis included Frequency, Percentage, Arithmetic mean, Standard deviation and Pearson’s correlation coefficient. The research findings indicate that 1) The overall competency of school administrators under the Ratchaburi Primary Educational Service Area Office 2 is at a high level 2) The overall effectiveness of schools under the same jurisdiction is also at a high level 3) The competency of school administrators has a statistically significant positive correlation with school effectiveness at the 0.01 level, indicating a strong and consistent relationship.